Identity complexities of symphony orchestras in Malaysia - Ng, Gerald Kea Chye (2014)
Symphony orchestras in Malaysia serve as an example where their organisational identity is neither sustained nor defined. In fact, they have had their identity altered and changed numerous times in their short history. The lack of consistency with the identity of any organisation could possibly lead to bigger problems for the organisation itself. Organisational identification is important because there is a relationship between identification and commitment towards the organisation. This will in turn create a positive outcome for work attitude and behaviours, which will have its implication on productivity, efficiency and, then, profit. The research designed for this research uses qualitative research methods such as passive observation, participant observation, semi-structured interview as well as document analysis. Samples and respondents were identified using predetermined criteria and depending on the receptiveness of the samples, both passive observation and participant observation was employed in order to obtain the data. Observations were conducted for an accumulative period of two [2] months to six [6] months determined on various factors such as rehearsal scheduled, concert schedule and approval of the orchestra administration and management. The two main perspectives of identity that is being studied with regards to symphony orchestras in Malaysia are firstly, how the identity of the orchestra is being perceived and secondly being how the identity of the orchestra is being portrayed. In order for this to be presented clearly, the active and passive factors that contribute to the portrayal of identity by the organisation and perception of the identity by the society is identified, observed, analysed and understood. Through this study it is identified that change of leadership figures, change of official names, economy and sponsorship as well as government policies are strong factors which indirectly affects the portrayal of identity of these orchestras as well as the perception of these orchestras by the society which houses them. With the case of the four orchestras being studied, it seems that an alteration or change in their core purpose of being established is inevitable when they are faced with a change of leadership figures. The economy, sponsorship and government policies have on the other hand altered the manner in which the orchestras operate which in turn will affect the portrayal and perception of the orchestras’ identity. It is essential for any form of arts to be independent from other influencing factors such as finance and infrastructure as the philosophy behind practicing art is about nurturing creativity. Thus it is found that it is more realistic for symphony orchestras to search for individualised solutions to their problems as the artistic needs of the orchestra as well as the society which houses them could potentially be different from others. Orchestras after all reflect, metaphorically, the functioning of social communication and mutual understanding which depends on democratic structures and rules within their artistic world as well as the community that houses them.